2005
DOI: 10.1021/ja0550935
|View full text |Cite
|
Sign up to set email alerts
|

Properties of a Mixed-Valence (FeII)2(FeIII)2 Square Cell for Utilization in the Quantum Cellular Automata Paradigm for Molecular Electronics

Abstract: The di-mixed-valence complex [{(eta(5)-C5H5)Fe(eta(5)-C5H4)}4(eta(4)-C4)Co(eta(5)-C5H5)]2+, 1(2+), has been evaluated as a molecular four-dot cell for the quantum cellular automata paradigm for electronic devices. The cations 1(1+) and 1(2+) are prepared in good yield by selective chemical oxidation of 1(0) and are isolated as pure crystalline materials. The solid-state structures of 1(0) and 1(1+) and the midrange- and near-IR spectra of 1(0), 1(1+), 1(2+), and 1(3+) have been determined. Further, the variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
100
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(101 citation statements)
references
References 53 publications
1
100
0
Order By: Relevance
“…[28] Mixed-valence squares are considered to have potential applications in the quantum cellular automata approach to nanoelectronics. [29] Discrete mixed-valence compounds are classified by using the Robin-Day criteria to constitute three main groups of complexes. Class I corresponds to species that show no electronic coupling (localized valence electrons) between metal centers.…”
Section: Electrochemistry and Mixed Valencementioning
confidence: 99%
“…[28] Mixed-valence squares are considered to have potential applications in the quantum cellular automata approach to nanoelectronics. [29] Discrete mixed-valence compounds are classified by using the Robin-Day criteria to constitute three main groups of complexes. Class I corresponds to species that show no electronic coupling (localized valence electrons) between metal centers.…”
Section: Electrochemistry and Mixed Valencementioning
confidence: 99%
“…At the same time, we can compare first oxidation potential for compounds 3 with that of cymatrene [9]. It is slightly shifted to the more anodic values for the compound 3 (see Table 2 couples might be detected in further experiments and were not observed in this studies due to previously reported problems such as absorption at the electrode surface [6].…”
Section: Electrochemistrymentioning
confidence: 61%
“…the same Cb-ligand [6]. An introduction of eCO 2 Et group in complex 2 shifts the oxidation potentials to the higher anodic values.…”
Section: Electrochemistrymentioning
confidence: 97%
See 1 more Smart Citation
“…For improvement in operation temperature and size of the devices, however, the idea of molecular quantum-dot cellular automata (molecular QCA) devices [5], in which a QCA cell constructed from small metallic dots is replaced by a single molecule, was proposed. Syntheses of tetranuclear complexes [6,7,8,9,10] and simplified dinuclear complexes [11,12], and single-molecule observation of the dinuclear complexes [13,14] have been investigated for the realization of molecular QCA devices. Also, theoretical simulations of QCA devices have been reported by many research groups [15,16,17,18,19,20,21].…”
Section: Introductionmentioning
confidence: 99%